2023
DOI: 10.1099/mgen.0.001045
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics of culture isolates and insect tissue illuminate the evolution of Wolbachia, Rickettsia and Bartonella symbionts in Ctenocephalides spp. fleas

Abstract: While fleas are often perceived simply as a biting nuisance and a cause of allergic dermatitis, they represent important disease vectors worldwide, especially for bacterial zoonoses such as plague (transmitted by rodent fleas) and some of the rickettsioses and bartonelloses. The cosmopolitan cat (Ctenocephalides felis) and dog (Ctenocephalides canis) fleas, as well as Ctenocephalides orientis (restricted to tropical and subtropical Asia), breed in human dwellings and are vectors of cat-scratch fever (caused by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Likewise, studies on C. felis injected with R. felis and using PCR showed that defensin-2, glycine-rich AMPs and several flea antigens were modulated by rickettsial infection [240]. Finally, apart from the bacterial pathogens transmitted, fleas are also known to have other bacteria in their microbiomes, but information is limited except that a diverse range of Wolbachia strains have been reported with unknown interactions with flea immunity and vector competence [244]. 1 and 3) There are ca.…”
Section: Fleas (Tablesmentioning
confidence: 99%
“…Likewise, studies on C. felis injected with R. felis and using PCR showed that defensin-2, glycine-rich AMPs and several flea antigens were modulated by rickettsial infection [240]. Finally, apart from the bacterial pathogens transmitted, fleas are also known to have other bacteria in their microbiomes, but information is limited except that a diverse range of Wolbachia strains have been reported with unknown interactions with flea immunity and vector competence [244]. 1 and 3) There are ca.…”
Section: Fleas (Tablesmentioning
confidence: 99%
“…Fleas (Siphonaptera) comprise a highly specialized order of holometabolous ectoparasitic insects with a cosmopolitan distribution and about 2700 species described so far [ 1 ]. In addition to being able to provoke bites and pruritic welts on the skin, these arthropods are also known to be vectors of different pathogens, responsible for causing a wide variety of diseases worldwide, including bartonellosis, rickettsiosis, and bubonic plague [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. This is due to the nature of some flea species, which present a low host specificity that facilitates the exchanging of microorganisms, posing a potential threat to the health of both humans and animals [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%